PELAKSANAAN PERJANJIAN PEMBORONGAN RUMAH PRIBADI SECARA LISAN BERDASARKAN HUKUM PERDATA DI KABUPATEN PELALAWAN - Nur Rabiah Mardatila; Firdaus Firdaus; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The house has now become a primary need for everyone, this causes many people who try to have a house to meet those needs, whether he builds himself or pays people to build the house or better known as the chartering agreement, in general this contracting agreement made verbally, causing many contracting parties to default, causing losses for those who bought up especially in Pelalawan Regency.The purpose of this study is to determine the factors that cause defaults in the contracting agreement, to find out the efforts that can be made to avoid the occurrence of defaults in the contracting agreement, as well as to determine the legal remedies that can be carried out by the contractor when the contractor occurs.This type of research is a sociological juridical study, this research was conducted in Pelalawan Regency, while the population and sample are all parties related to the problems examined in this study, data sources used, primary data, secondary data, and tertiary data, collection techniques data in this study with interviews and literature review.The cause of defaults in the contracting agreement is the contracting agreement made verbally, the weak goodwill of the contractor, the weak understanding of the contractor in the field of construction, the weak understanding of the legal parties. efforts that can be made to avoid defaults in the contracting agreement, contractual agreement made in writing, the good faith of the parties must be increased in understanding the contractor in the field of construction, increase the understanding of the parties' law.It is expected that the parties will enter into an agreement in writing, and in the implementation of the agreement in good faith, broaden the legal perspective, especially in the area of the agreement. It is expected that the contractor will add his insight in the construction sector.Keywords: Private Contracts - Chartering - Private Houses - Civil Law